Kinetics of the reactions of Cl atoms with CF3C(O)OCH3, CF3C(O)OCH2CH3, CF2HC(O)OCH3 in the temperature range of 287-313K and 1 atm - Blanco, Maria Belen (2015)
Rate coefficients of the reactions of Cl atoms with CF3C(O)OCH3 (k1), CF3C(O)OCH2CH3 (k2) and CF2HC(O)OCH3 (k3) have been measured for the first time in the temperature range of 287–313 K and 1 atm. Temperature dependencies of k are described by the Arrhenius expressions: k1 = (5 ± 2) × 10−12 exp[−(1216 ± 72)/T] (cm3 molecule−1 s−1), k2 = (539 ± 164) × 10−12 exp[−(1637 ± 94)/T] (cm3 molecule−1 s−1) and k3 = (20 ± 9) × 10−12 exp[−(1368 ± 82)/T] (cm3 molecule−1 s−1). The kinetic data are compared with previous theoretical calculations and a correlation between kCl and EHOMO of the halogenated VOC is presented.